Up-hill diffusion of solute atoms towards slipped grain boundaries: A possible reason of decomposition due to severe plastic deformation. (November 2020) - Kovács, Zsolt; Chinh, Nguyen Q.
Abstract: Supersaturated solid solutions subjected to severe plastic deformation often exhibit decomposition of the solid solution, leading to a peculiar grain boundary phenomenon, the formation of few nanometer thin layer enriched in solute atoms along grain boundaries. Based on localized grain boundary sliding, this phenomenon can be explained by the formation of hydrostatic stress field, which induces up-hill diffusion in the solute atmosphere, resulting in solute atom accumulation along the stressed grain boundaries. Graphical abstract: Image, graphical abstract